Photon Induced Current Modulation in Nanoscale FETs simulated using ATHENA and ATLAS - Mohd Taufik Bin Ibrahim, Mohd Taufik (Universiti Teknologi Petronas, 2009)
Field Effect Transistor (FET) was based on the electric field to control the conductivity of channel for the carrier in semiconductor material. Nowadays, the trend to miniaturize the FET to nanoscale FET has been rapidly develops. In nanoscale FET it exhibits the quantum effect which is tunneling. Light illuminated on the surface of conductor can generate electron hole pairs thus; light penetrating into the Single Electron Transistor (SET) can give big influences to the electrical characteristics because the size of SET is very small. Addition of single charge will sensitively modulate the current flow at the top silicon channel. Thus it can be developed into single charge detector. In the conventional photodetector, it cannot detect a single photon, thus based on the sensitivity of SET it can be developed to be used as the single photon detector. In our work, we would like to see the effect of photon induced charge in the silicon-on-insulator SET. This effect will be simulated in the device simulation software, where the interface charge will act as the electron-hole pairs that were generated from light illumination. The findings shows the unexpected results, whereby the interface charge that introduce inside the Silicon-on-Insulator Field Effect Transistor (SOIFET) model do not give any changes to the energy band.